Efektifitas Kelas Ibu Hamil terhadap Pengetahuan Kesehatan Ibu Hamil Selama Hamil di Wilayah Puskesmas Pekauman Banjarmasin (Journal Genta Kebidanan, 2024)
Background : Pregnancy is a period of growth and development of the fetus towards birth. Knowledge is one of the factors that influence the formation of health behavior. If pregnant women know and understand good health behavior, then you can avoid various diseases or complications and the risk of decreasing health. The class for pregnant women also contains information or activities that can be obtained by pregnant women in the class for pregnant women. Objective : Knowing effectiveness of pregnant women classes on the health of pregnant women during pregnancy in the working area of the Pekumaman Public Health Center, Banjarmasin. Methods : This type of research is analytic descriptive with a cross sectional approach. A sample of 32 people was obtained with the sampling technique using total sampling. Results : The results of this study found that that respondents who actively attended classes were pregnant women as much 20 person (62,5%) who passively attend classes pregnant women as much 12 person (37,5%) and as many knowledgeable respondents 10 person (31.25%) and knowledgeable respondents quite a lot 18 person (56,25%), while respondents who are knowledgeable less as much 4 person (12.5%). Results Chi-square test shows p-value as much 0,237 (
Keywords: Pregnancy Class; Health Knowledge of Pregnant Women